(untitled) (Jalalabad Medical Journal, 2025)
Cor triatriatum is a rare congenital heart defect, while secundum atrial septal defect (ASD) is a relatively common congenital heart defect. Primary symptoms in an older patient may mimic reactive airway disease if the diagnosis is not made in infancy. We report a case of cor triatriatum sinister in a 2 year old child, previously diagnosed with recurrent upper respiratory tract infection (RTI), presenting to a paediatrician. The initial response to treatment with bronchodilators and corticosteroids was not responding, prompting a thorough evaluation. Subsequent imaging was done and diagnosed as cor triatriatum sinister with secundum ASD. When patients with this type of scenario do not respond adequately to classical conservative management, it would be better for a clinician or paediatrician to look for an alternative diagnosis, as in this case. Jalalabad Med J 2024; 21 (1): 23-25